A case report of a 30-year-old male with megacystis-microcolon-intestinal hypoperistalsis syndrome with de novo ACTG2 gene mutation - Knežević Violeta V.; Knežević Aleksandar D.; Milijašević Dragana S.; Božić Dušan Đ.; Milijašević Boris Ž. (Srpsko lekarsko drustvo, 2023)
Introduction: Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a very rare genetic disorder of visceral motility of the gastrointestinal and genitourinary system. According to our knowledge, so far there has been no description of a patient with megacystis-microcolon-intestinal hypoperistalsis syndrome and chronic secretory diarrhea. Case report: We have presented a case report of a 30-year-old male with a genetically verified novel (de novo) mutation p.R257H in the smooth muscle actin (ACTG2) gene. At 8 months of age he was diagnosed with suspected Hirschsprung's disease, partial resection of the colon was performed. During the first year of his life, subtotal colectomy with cecorectal anastomosis was performed and, simultaneously, deteriorated emptying of the urinary bladder was confirmed. The patient was subjected to several unsuccessful abdominal and urological operations. At age of 18, the differential diagnosis was narrowed to micro-villus inclusion disease and congenital chloride diarrhea. The patient was tolerant to oral feeding all the time, where intermittent parenteral nutrition started only in adolescence. At the age of 26, due to urethral stenosis, perineal urethrostomy was performed. Since the age of 29, due to complications of the underlying disease the patient was administered chronic dialysis treatment, and a year later, genetic testing provided the definitive diagnosis of MMIHS. Therefore, combined kidney and intestinal transplantation was proposed. The patient continued the treatment with daily fluid and electrolyte compensation along with adequate parenteral nutrition through a triple-lumen central catheter. Conclusion: Timely genetic testing leads to avoiding repeated surgical interventions and numerous complications. Multivisceral transplantation represents a significant improvement in the treatment of patients with this syndrome.